Capitalism, the Book of Amos and Adam Smith: An analysis of corruption - Mark Rathbone (HTS Teologiese Studies/Theological Studies, 2020)
The purpose of this study is to challenge the criticism of capitalism by biblical scholars that is based on references to the prophetic tradition in the Old Testament and specifically the Book of Amos. In many of these reflections, capitalism is viewed as a corrupt and morally dysfunctional system that perpetuates economic injustice. In order to challenge these perspectives, the prophet Amos and Adam Smith (to whom the legacy of capitalism is generally traced) will be compared in terms of their understanding of corruption as an economic phenomenon and pressing problem in South Africa. This will be done to argue that both Amos and Smith, although from two distinct theoretical and historical perspectives, use similar analytic criteria to study corruption. Smith and Amos followed a dual view of corruption in which convictional decline took place. For Amos, the convictional dimension was represented specifically by a decline in belief in God and for Smith, by a decline in the values of the Enlightenment, such as liberty and equality; and at the same time, the moral dimension was represented by moral failure in terms of non-compliance with the law (תֹּרָה, tôrâh) of God (Amos 2:4) and corrupt practices by citizen and government officials (Smith). Amos notes that there is a theological deficit at the root of economic injustice that results in the selling (מָכַר, mâkar) of the righteous (צַדִּיק, tsaddı̂yq), the needy or beggar (אֶבְיוֹן, ‘ebyôn) and the dependent or weak (דַּל, dal) for private gain (Am 4:6). Law in the context of Amos is not only viewed as a moral imperative but the foundational principle of the structure of society (like liberty and freedom was for Smith). Therefore, a general criticism of capitalism based on moral failure and lack of conviction from Amos cannot be convincingly argued because Smith uses the same criteria. Criticism of capitalism should be more precise in terms of the loss of conviction and moral failures that Smith highlighted.